Night moves: nocturnal movements of endangered spotted turtles and Blanding's turtles. (7th October 2021) - Hjort Toms, A.; Browning, L. V. T.; Paterson, J. E.; Angoh, S. Y. J.; Davy, C. M.
Abstract: Diel activity patterns in animals can be diurnal (concentrated during daylight), nocturnal (concentrated during darkness), cathemeral (both daylight and darkness) or crepuscular (concentrated at twilight). Freshwater, Nearctic turtles are typically considered diurnal, apart from crepuscular or nocturnal nesting migrations by mature females. However, some crepuscular and nocturnal activity has been observed in non‐nesting freshwater turtles. There are no quantitative studies of nocturnal movements in freshwater turtles, but GPS‐tracking devices provide an opportunity to collect and archive locations for 24 h, providing the GPS antenna is exposed above water. We collected GPS locations and shell temperatures from mature spotted turtles ( Clemmys guttata, n  = 12) and Blanding's turtles ( Emydoidea blandingii, n  = 12) from May to July 2018 in southern Ontario, Canada. We compared the minimum distance moved by turtles during the day and night, and we tested previously proposed hypotheses that nocturnal movement is linked to nesting or thermoregulatory benefits. Blanding's turtle movements were primarily diurnal, but spotted turtles were cathemeral. Nocturnal activity by spotted turtles was not restricted to the nesting season and did not confer thermoregulatory benefits. We hypothesize that nocturnal exposure and movement by spotted turtles provide increased time for foraging or mate‐seeking, allowing daytime hours to be used for basking. Our study demonstrates cathemeral diel patterns in spotted turtles and quantitatively tests hypotheses about the drivers of nocturnal behaviour in freshwater turtles. Future research should use observational methods in order to better understand the purpose of nocturnal activity in Nearctic, freshwater turtles. Abstract : There have been no quantitative studies of nocturnal movements in freshwater turtles, but GPS‐tracking devices provide an opportunity to collect such data. We used GPS‐tracking devices to investigate whether two endangered freshwater turtles (spotted turtles and Blanding's turtles) were active at night. Both male and female Spotted turtles were active at night, moving similar distances within a night and within a day. Blanding's turtles were not very active at night and most movement occurred during the day.